Training the buffalo (Bubalus bubalis) as a work animal (Revista Sistemas de Producción Agroecológicos, 2018)
In regions of Asia and South America, the buffalo (Bubalus bubalis) has been used for centuries to provide workforce, in the modalities of loading, shooting or mounting, and even in the mechanization of soils with flood characteristics (rice crops), where the mud can reach a depth that reaches 40 to 60 cm, they can move at a speed of 6-8 km/h, and can reach loads of up to 1500 kg, with work performance of 0.25 hectares per day. It was also observed that the force exerted by buffaloes as working animals does not represent restrictions when using them in different agricultural work within the farms, and its clear adaptation to the tropics allows an adequate physical development, facilitating its training. It is considered as an "appropriate technology", the system that uses the trailer and buffalo combination, because it exceeds the effectiveness of the machinery in productivity and operating costs, which has generated that, in the palm plantations at the time of harvest, the buffaloes are used as the main source of traction for the trailers that store this fruit. In spite of the existence of cattle and African palm producing areas, in Colombia, no studies have been documented where the training processes of the buffalo are related through the implementation of rational dressage, to use them as work animals, therefore, the objective of this work is to expose the qualities of this species, and the appropriate techniques for the training and management of buffaloes intended for work, based on its ethology and rational treatment. It has been recognized that the implements and installations used in the management of buffaloes are important to facilitate training, which should be comfortable in the case of head restraint, nose ring is used in the nose, also ties of different calibers and a poppet are used, but in no case should harm be inflicted; in work activities the saddle, the carpet and the trailer are used, which should not limit the locomotion of the buffalo. Daily and during milking it is necessary to devote 20 to 30 minutes to the manipulation of the buffalo to have contact and establish a link with the person who is training him. To allow control and to guide the animal, in this stage he is taught some orders with the trapping bow and with the voice, pulling it from the head rope attached to the nose ring; buffaloes should be exercised through walks between one to two hours. At the work site the animal is guided, always with the tamer ahead to show him the roads and show him the streets; this accompaniment may vary in terms of duration, because with some buffaloes it can take months and in others less, in general, voice orders are reinforced until the animal is brought to work with only one person.
Keywords: rational dressage; animal traction; ethology; bovids; palm